Hieroglyphic Writing - Dvořák, Tomáš (Teorie vědy / Theory of Science, 2017)
The article discusses and critically reinterprets Carlo Ginzburg’s concept of the indexical paradigm in human sciences. It situates the method of reading insignificant details as indicators of an imperceptible reality into historical, cultural and technical context through examples of medical diagnosis and art connoisseurship. It traces links between the development of literacy, script, and graphology in the 19th century and the emergence of technical forms of inscription (self-registering instrument), which brought new methods of interpretation and analysis into many fields and challenged traditional boundaries between natural, social, and human sciences.